PENGARUH PROPORSI SUKROSA-ISOMALT TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK PERMEN JELLY ANGGUR BALI (Alphonso lavalle) - Susilo, Ivone; Suseno, Thomas Indarto Putut; Kuswardhani, Indah (Jurnal Teknologi Pangan dan Gizi, 2013)
Jelly candies has a clear transparent appearance and resilience texture with variety colors and sweet taste. Natural colorant can be used in jelly candies are anthocyanins contained in Bali grapes. Isomalt can be used as alternative sweetener in jelly candies as it can form the body and has a sweet taste without after-taste. Isomalt is more stable at higher temperatures and more resistant to hydrolysis by enzymes and acids than sucrose, but with a lower solubility. The different properties of sucrose and isomalt can cause changes in the physicochemical and organoleptic characteristics of jelly candies that need to be investigated the right proportion of sucrose-isomalt. The research design used is Randomized Block Design with a single factor. Isomalt concentrations used were 0%, 5%, 10%, 15%, 20%, 25% with four repetitions for each treatment. The parameters tested include the physicochemical properties of the water content, pH, texture (firmness and tensile strength) and organoleptic properties (color, flavor, and texture). Based on statistic analysis, different proportion of sucrose and isomalt gave significant effect (Î±=5%) on water content, firmness, elasticity, organoleptic test taste and texture but color was not significantly influenced. The higher proportion of isomalt increased water content and firmness of jelly candies, but decreased tensile strength. Treatment isomalt 20% gives the best result based on additive weighting, have 19,18% water content, 14,62 N/10 mm firmness, 119,14 mm tensile strength, the preferance score of color was 3,59, taste was 3,71, texture was 3,60.